Citicoline in neurology and psychiatry: Citicoline in medicine - Pavlovic, Aleksandra; Pavlovic, Dragan; Totic, Sanja; Lackovic, Maja; Bozic, Marija; Djordjevic, Jelena (Engrami, 2024)
Citicoline is a supplement-nootropic with potential applications in treating various neurological, psychiatric, and other conditions. There is experimental and clinical evidence of the benefits of citicoline in individuals after stroke, traumatic brain injury, and cognitive decline of various etiologies. Preclinical studies suggest that citicoline has neuroprotective and neurorestorative effects, which can be explained by its antioxidant, anti-inflammatory, and metabolic actions. Citicoline is necessary for the synthesis and stabilization of biological membranes, improves mitochondrial function, and is crucial in the synthesis of acetylcholine and other neurotransmitters in the central nervous system. No specific drugs are available for treating cognitive sequelae of stroke and traumatic brain injury. In experimental and clinical studies, citicoline has shown a safe profile with positive clinical effects on overall cognitive abilities, attention, executive function, and mood. There are also positive results of its use in patients with neurodegenerative diseases, although on a small number of participants. In psychiatry, the beneficial effects of citicoline on depression, negative symptoms of schizophrenia, and substance use disorders are described. This review provides an overview of the mechanisms of action of citicoline and summarizes the published research on its use in neurology and psychiatry.
Keywords: Citicoline, acethylcholine, stroke, dementia, cognition, psychiatry